#TITLE_ALTERNATIVE# - LARASSATY PUTRI PRATAMI (NIM : 12214062 ), FATIMAH
In hydraulic fracturing stimulation of shale gas reservoir, the fracture network created by the geometrical dimensions of horizontal well and fracture parameters, such as lateral length, fracture spacing, and fracture halflength,will represent the stimulated reservoir volume (SRV). SRV value is becoming a key measure in reservoir modelling to optimize well productivity and estimate ultimate recovery. However, approximation of SRV usually requires microseismic and other dataset which are usually limited in real-life shale field. This paper focuses on the estimation of SRV values of shale gas reservoir by quantification of drainage volume (DV) using pressure drawdown analysis, of which is a common method to determine initial gas in-place (IGIP) in conventional gas reservoirs. Initially, sensitivity studies are carried out to evaluate the effect of well and fracture parameters on SRV. Pressure profiles during pseudo-steady period and SRV values obtained from simulator are used to obtain the DV values. A mathematical correlation is established from multivariate regression of SRV, DV, and well and fracture parameters for quick calculation of DV with various well and fracture parameters values. SRV and DV calculated from correlation are then compared, and a second correlation that serves as correction factor to calculate SRV is established to account for the difference of both volume parameters, as in essence SRV and DV are rarely deemed to be similar in unconventional reservoirs. The relationship between SRV and DV values will be presented as a final result of this study. Haynesville Shale properties will be incorporated into the simulation work, tailoring this analysis to any shale reservoir with similar producing environments. This study provides significant reference for SRV calculation derived from pressure drawdown analysis that will reflect and represent more accurate estimates despite the limitations on the available reservoir data.